Electrochemical behavior of a nitrobenzenesulfonyl derivative of aniline in aqueous solution - Boldrin Zanoni, M. V. [UNESP]; Rosa, I. L V; Pesquero, C. R.; Stradiotto, Nelson Ramos [UNESP] (FapUNIFESP (SciELO), 1997)
The electrochemical behavior of aniline protected by a nitrobenzene sulphonyl group in aqueous solution at a mercury electrode is reported. At pH < 10 the compound was reduced in a single well-defined step. Reduction of the nitro group involving a preceding protonation step was postulated. Two reduction steps are present at higher pH (pH > 11). Controlled potential electrolysis confirms that the reduction of the nitro group in a four-electron step to N-phenyl-4-hydroxylamine sulphonamide is always the preponderant process. ©1997 Soc. Bras. Química.
Keywords: Amine improtection; Cathodic cleavage; Nitrobenzenesulphonamide